Respuesta :
Answer:
3
Step-by-step explanation:
[tex]y+\frac{y-3}{3} \\=\frac{3y+y-3}{3}\\=\frac{4y-3}{3}[/tex]
Following are the calculation of the common denominator:
Given:
[tex]\bold { \frac{y + [ \frac{(y - 3)}{3}]}{(\frac{5}{9} + \frac{2}{3y})}}[/tex]
To find:
common denominator=?
Solution:
[tex]\to \bold { \frac{y + [ \frac{(y - 3)}{3}]}{(\frac{5}{9} + \frac{2}{3y})}}[/tex]
Let Multiply and divide the above equation with '9y':
[tex]= { \frac{9y}{9y} \cdot \frac{y + [ \frac{(y - 3)}{3}]}{(\frac{5}{9} + \frac{2}{3y})}}\\\\= { \frac{y \cdot 9y + y\cdot 9y- \frac{3}{3}]} { 9y(\frac{5}{9}) + 9y(\frac{2}{3y})}}\\\\={ \frac{y \cdot 9y + 3y(y-3)} { 9y(\frac{5}{9}) + 9y(\frac{2}{3y})}}\\\\={ \frac{y \cdot 9y + 3y(y-3)} { y \cdot 5 + 9y(\frac{2}{3y})}}\\\\={ \frac{9y^2 + 3y^2-9y} { 5y + 6}}\\\\={ \frac{12y^2 -9y} { 5y + 6}}\\\\[/tex]
Therefore, the common denominator is "5y + 6".
Learn more:
brainly.com/question/20993316